REFLECTION AND REFRACTION OF AN ELECTROMAGNETIC WAVE ON A TWO-LAYER MAGNETIC STRUCTURE - Valikhanov, Nuriddin Kamoliddin o‘g‘li; Saydalieva, Shaxlo Samikovna (Innovative Development in Educational Activities, 2023)
In the study of nanostructures, the study of multilayer magnetic structures is of great importance. In this paper, we will consider a two-layer magnetic structure, the first layer of which is a film with a thickness ℓ magnetized in equatorial geometry, and the second layer is a substrate magnetized in polar geometry.